Isolated testicular pain mimicking ruptured abdominal aortic aneurysm in a nonagenarian - Regus, Susanne; Apel, Hendrik; Dankerl, Peter; Lang, Werner (American Journal of Emergency Medicine, 2015)
Ruptured abdominal aortic aneurysm commonly presents as acute abdominal or lower back pain and hemodynamic instability. We discuss the case of a 90-year-old patient who presented to the emergency unit with a 3-day history of left testicular pain. Ultrasound scan demonstrated and a computed tomography scan confirmed a 6 cm in diameter ruptured abdominal aortic aneurysm with enlargement and hematoma of the left psoas muscle causing the symptoms. This atypical presentation highlights the need for clinical vigilance and emergency physician-performed ultrasound scan in the older patients with seemingly benign testicular symptoms.
EVALuna2:14469